Evaluating the implementation of a multi-level mHealth study to improve hydroxyurea utilization in sickle cell disease - Hankins, J. S; Potter, M. B; Fernandez, M. E; Melvin, C; DiMartino, L; Jacobs, S. R; Bosworth, H. B; King, A. A; Simon, J; Glassberg, J. A; Kutlar, A; Gordeuk, V. R; et al. (Frontiers in Health Services, 2023)
Background Sickle Cell Disease (SCD) is a progressive genetic disease that causes organ damage and reduces longevity. Hydroxyurea is an underutilized evidence-based medication that reduces complications and improves survival in SCD. In a multi-site clinical trial, part of the NIH-funded Sickle Cell Disease Implementation Consortium (SCDIC), we evaluate the implementation of a multi-level and multi-component mobile health (mHealth) patient and provider intervention to target the determinants and context of low hydroxyurea use. Given the complexity of the intervention and contextual variability in its implementation, we combined different behavioral and implementation theories, models, and frameworks to facilitate the evaluation of the intervention implementation. In this report, we describe engagement with stakeholders, planning of the implementation process, and final analytical plan to evaluate the implementation outcomes. Methods During 19 meetings, a 16-member multidisciplinary SCDIC implementation team created, conceived, and implemented a project that utilized Intervention Mapping to guide designing an intervention and its evaluation plan. The process included five steps: (1) needs assessment of low hydroxyurea utilization, (2) conceptual framework development, (3) intervention design process, (4) selection of models and frameworks, and (5) designing evaluation of the intervention implementation. Results Behavioral theories guided the needs assessment and the design of the multi-level mHealth intervention. In designing the evaluation approach, we combined two implementation frameworks to best account for the contextual complexity at the organizational, provider, and patient levels: (1) the Consolidated Framework for Implementation Research (CFIR) that details barriers and facilitators to implementing the mHealth intervention at multiple levels (users, organization, intervention characteristics, broader community), and (2) the Technology Acceptance Model (TAM), a conceptual model specific for explaining the intent to use new information technology (including mHealth). The Reach Effectiveness Adoption Implementation and Maintenance (RE-AIM) framework was used to measure the outcomes. Discussion Our research project can serve as a case study of a potential approach to combining different models/frameworks to help organize and plan the evaluation of interventions to increase medication adherence. The description of our process may serve as a blueprint for future studies developing and testing new strategies to foster evidence-based treatments for individuals living with SCD.